Utilization of Banana Leaves for Environmentally Friendly Crafts as an Effort to Reduce Organic Waste in Kaujon, Serang, Banten - Nabila, Dewi Alimah Alya; Melati, Intan; Salsabilah, Amirah Puti; Azzahra, Fatima; Fitroh, Nur Santika; Fitriana, Desi Eka Nur (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Banana leaching waste is one of the abundant organic waste in Indonesia but has not been used optimally. In fact, this material has the potential to be an economically valuable and environmentally friendly resource. This research aims to find out the form of utilization and treatment techniques of banana peel waste as basic materials for handicrafts and to examine its development potential in improving the welfare of the people in Kaujon, Serang, Banten. The method used is qualitatively descriptive with a purposive sampling approach. Data was collected through interviews, observations, and documentation of banana peelers at the Main Source of Craft Indonesia, then descriptively analyzed. Research results show that craftsmen use two types of banana leaches, namely Pisang Kepok (Musa Paradisiaca Var. Balbisiana colla) and Pisang Klutuk (Musa balbisiana Colla), with kepok types, are more dominant because the fibers are strong and easy to process. The products produced include flower vases, piggy banks, bedclothes, tissue boxes, and flower decorations. This utilization has a positive impact on the economy by increasing the income of craftsmen, as well as on the social by fostering independence and environmental awareness of the community. Banana leaching waste treatment in Kaujon, Serang, Banten is effective in reducing organic waste as well as opening up new economic opportunities, thus contributing to environmental conservation and sustainable development based on local potential.